PELAKSANAAN HIGIENE PENJAMAH MAKANAN DAN SANITASI LINGKUNGAN DI INSTALASI GIZI RUMAH SAKIT HOLISTIC PURWAKARTA TAHUN 2016 - Nurseha, Ela; Haryanto, Irwan; Torina, Dian Titis (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2017)
Background: In food hygiene and sanitation activities in hospitals, hygiene of foodstuffs processed as food for inpatients. Diseases transmitted through food may cause mild disease and severe and even lead to death of them caused by the application has not been good as SOP (Standard oprating Procedure). Objective: To describe efforts to implement hygiene and sanitation in the hospital holistic nutrition installation purwakarta. Methods: The study design was observational descriptive design. 13 research subjects food handlers 2 nutritionists and 11 food handlers in the installation of Holistic Nutrition Hospital Purwakarta. Data execution of hygiene and sanitation installations home nutrition tabulated data and analyzed descriptively. Results: The observation of hygiene and sanitation requirements 100% memmenuhi Decree No. 1096/Menkes/Per/VI/2011 and SOP (Standard oprating procedure). Physical acceptance tests for hygiene and sanitation at the plant nutrition Holistic Hospital Purwakarta getting the 83 or 92% according to the group B, the minimum value of the maximum 83 92, or ranking 83-92%. Conclusion: Environmental sanitation: building, room food processing, sanitary aspects hospitals, materials sanitaiser, sanitaiser equipment and hygiene of food handlers: Health handlers, use of PPE, behavior penjamaha food already eligible under Decree No. 1096/Menkes/Per/VI/2011 and SOP (Standard oprating procedure). Acceptance and implementation of hygiene and sanitation jasanoga class B, a minimum of 83 maximum value of 92, or ranking 83-92%.